Keteladanan Guru Akidah Akhlak Dalam Membentuk Karakter Siswa Mts Swasta Jam’iyah Mahmudiyah Tanjung Pura - Marhan Hasibuan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
Identification of the problems found at the research location, namely: 1. Students are less active in participating in Akidah Akhlak lessons in the form of active discussions, actively asking or answering questions, actively giving opinions regarding the implementation of learning and teaching activities carried out online or online. 2. Students lack interest in learning in the subjects of Akidah Akhlak so that students do not understand the material of student moral development. 3. Teachers in the field of Akidah Akhlak have not implemented innovative and creative learning strategies in classroom teaching activities so that students are not actively involved in learning activities. The type of research used in this research is Classroom Research (Elfanany, 2014) with a field approach (field research), namely the researcher tries to maximally reveal facts, qualitative research is carried out. natural and man-made phenomena (Moleong, 2010). The subjects in this study were the head of the Madrasah, teachers of Akidah Akhlak studies, school operational staff and students. The sources of data in the implementation of this research are the head of the Madrasa as the subject as well as the object of research and the teacher of Akidah Akhlak in MTs. Private Jam'iyah Tanjung Pura. Data analysis techniques: 1) observation, 2) interviews, and 3) documentation. Test the validity of the data in this study using a credibility test conducted by triangulation. The results of the study show: (1) Learning and teaching activities in the field of Akidah Akhlak study class VII private MTs Jam'iyah Mahmudiyah Tanjung Pura have been running effectively and efficiently. Although learning and teaching activities are carried out with strict attention to health protocols, learning is still carried out online (in the network) and offline (outside the network), (2) the example of teachers in the field of Akidah Akhlak studies has played a very important role in carrying out the learning system, especially in shaping character. student learning grade VII MTs. Private Jam'iyah Mahmudiyah Tanjung Pura, (3) The process of character building for grade VII students of Private Jam'iyah MTs Tanjung Pura has been running effectively and efficiently, as evidenced by the results of observations at the research location and the results of interviews with informants that the example of a teacher of Akidah Akhlak can shape character. student learning, especially in the field of study of Akidah Akhlak.